Pengaruh Tingkat Pendidikan, Modal dan Teknologi Terhadap Daya Saing Usaha Mikro, Kecil dan Menengah (UMKM) di Kecamatan Sawan - Kariyani, Ni Nyoman Yuni; Meitriana, Made Ary (Universitas Pendidikan Ganesha, 2022)
The purpose of this study is to determine (1) the effect of the level of education, capital and technology partially on the competitiveness of micro, small and medium enterprises (MSMEs) in Sawan District, (2) the influence of the level of education, capital and technology simultaneously on business competitiveness. micro, small and medium enterprises (MSMEs) in Sawan District, (3) the magnitude of the influence of the level of education, capital and technology on the competitiveness of micro, small and medium enterprises (MSMEs) in Sawan District. This type of research is causal research with a quantitative approach. The population in this study were all formal MSMEs in Sawan District, Buleleng Regency as many as 2,365 with a sample of 343 respondents who were determined using the Slovin formula. Data collection methods used are interviews and questionnaires. Then, the data analysis technique used is multiple linear regression analysis. The results of this study indicate that (1) there is a partially significant influence between the level of education, and capital on the competitiveness of micro, small and medium enterprises (MSMEs) in Sawan District. Meanwhile, technology does not affect the competitiveness of micro, small and medium enterprises (MSMEs) in Sawan District, (2) there is a simultaneous significant effect between the level of education, capital and technology on the competitiveness of micro, small and medium enterprises (MSMEs) in Sawan District, (3) the magnitude of the influence of the level of education, capital, and technology on the competitiveness of MSMEs is 51.3% while 48.7% is influenced by other variables not tested in this study.